2018
DOI: 10.1002/2017gl076825
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Signatures of Lead in the Northeast Atlantic

Abstract: Anthropogenic activities have resulted in enhanced lead (Pb) emissions to the environment over the past century, mainly through the combustion of leaded gasoline. Here we present the first combined dissolved (DPb), labile (LpPb), and particulate (PPb) Pb data set from the Northeast Atlantic (Celtic Sea) since the phasing out of leaded gasoline in Europe. Concentrations of DPb in surface waters have decreased by fourfold over the last four decades. We demonstrate that anthropogenic Pb is transported from the Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 70 publications
1
39
0
Order By: Relevance
“…(SI , Table S3). While DPb and DAl distributions are known to be influenced by atmospheric inputs, sediment supply, and scavenging Menzel Barraqueta et al, 2019;Rusiecka et al, 2018), an association of Al with diatom frustules (Menzel Barraqueta et al, 2018), and Pb with organic matter remineralization and sediment supply (Rusiecka et al, 2018)…”
Section: 1029/2020gb006674mentioning
confidence: 99%
See 1 more Smart Citation
“…(SI , Table S3). While DPb and DAl distributions are known to be influenced by atmospheric inputs, sediment supply, and scavenging Menzel Barraqueta et al, 2019;Rusiecka et al, 2018), an association of Al with diatom frustules (Menzel Barraqueta et al, 2018), and Pb with organic matter remineralization and sediment supply (Rusiecka et al, 2018)…”
Section: 1029/2020gb006674mentioning
confidence: 99%
“…In recent years, large new data sets have emerged as part of the international GEOTRACES program (Henderson et al, 2007;Schlitzer et al, 2018). The availability of oceanic Fe data has substantially improved (e.g., Fitzsimmons et al, 2017;Milne et al, 2017;Tagliabue et al, 2012), with also some new data sets for, for example, Zn (Middag et al, 2019;Wyatt et al, 2014), Al (Measures et al, 2015;Menzel Barraqueta et al, 2018), Pb (Noble et al, 2015;Rusiecka et al, 2018), Cd (Middag et al, 2018;Wu & Roshan, 2015), and Ni (Middag et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration range and depth distribution is similar to reported distributions further offshore at about 21°W (Noble et al, 2015). These authors suggested that increased concentrations of up to 70 pmol L -1 between 600 and 800 m depth were related to the influence of (Rusiecka et al, 2018). The major source of Pb to the ocean is atmospheric dust deposition from anthropogenic emissions (Bridgestock et al, 2016;Nriagu and Pacyna, 1988;Veron et al, 1994) with a recent indication of reduced anthropogenic Pb inputs to surface waters in the eastern tropical Atlantic under the North African dust plume (Bridgestock et al, 2016).…”
Section: Spatial Distributions Of Dissolved and Leachable Particulatementioning
confidence: 99%
“…Ideally, a study such as that performed by Du et al () for Nd isotopes would allow for the quantification of porewater control on the archived Pb signal. Unfortunately, core top sediments integrate over decades to centuries, while anthropogenic Pb inputs varied considerably over these time scales: increasing with the onset of industrial activity and the use of leaded gasoline and more recently decreasing with the implementation of environmental regulation and phasing out of leaded gasoline (Rusiecka et al, ). This is particularly true for the Mediterranean as it experiences a larger human impact by volume relative to the Atlantic or Pacific.…”
Section: Resultsmentioning
confidence: 99%